The Durability of Zirconia/Resin Composite Shear Bond Strength using Different Functional Monomer of Universal Adhesives - Klaisiri, Awiruth; Krajangta, Nantawan; Thamrongananskul, Niyom (European Journal of Dentistry, 2021)
Objective This study examined the effectiveness of different functional monomers in universal adhesives on zirconia/resin composite bond strength both before and after thermocycling. Four universal adhesives (G-premio bond universal, GPU; Clearfil Tri-S bond universal, CTB; Optibond Universal, OBU; Tetric N-bond universal; TNU), one adhesive (single bond 2; SB2), and one ceramic primer (Clearfil ceramic primer plus, CCP) were used in this study.Materials and Methods Zirconia discs were prepared and embedded in acrylic. Specimens were polished and sandblasted with alumina. The specimens were randomly divided into two groups (24 hours and the thermocycled), and each group was divided into six subgroups (n = 10), according to zirconia surfaces treatments: no Tx, CCP + SB2, GPU, CTB, OBU, TNU. An Ultradent mold was located on top of the treated zirconia surface. The resin composite was filled into the mold and then light-cured. A universal testing device was used to determine the shear bond strength.Statistical Analysis The data were statistically analyzed using one-way ANOVA and Tukey's test.Results After water storage for 24 hours, the shear bond strengths were GPU > CCP + SB2 = CTB = OBU = TNU > no Tx (p < 0.05). After thermocycling, the shear bond strengths were CCP + SB2 = GPU = CTB = TNU > OBU > no Tx (p < 0.05).Conclusion The universal adhesives containing 10-MDP exhibited the best performance in the shear bond strength of the zirconia/resin composite interface both before and after thermocycling.
Keywords: resin composite; shear bond strength; universal adhesive; zirconia